Independência do Banco Central no Brasil : a rotatividade dos diretores do COPOM e os agregados monetários na determinação das taxas de juros (2001-2011) - Santos, Allan Silveira dos (2013)
The main objective of this dissertation is to analyze the role of central bank independence (CBI), the programming monetary under the targeting regime and the function of these instruments on the control of prices. In order to test empirically the question of (IBC) in Brazil, two reaction functions are estimated for the BCB: the first aims to identify whether the turnover of the Directors of the Monetary Policy Committee (COPOM), interfered in the conduct of monetary policy. The second application aims to identify the reaction of monetary authorities to the deviations from predicted values of M1 in relation to established goals. Regarding the theoretical goals is possible to conclude from the study that although the empirical studies are not conclusive about the existence of a statistically significant and negative relationship between inflation and the degree of central bank independence, however, there are important theoretical arguments that confirm the independence as an important factor for maintaining inflation at low levels. The results obtained through the reaction function indicate that changes of directors of the (COPOM) did not result in marked changes in the conduct of monetary policy in Brazil. However, through the structural VAR model was possible to observe a positive and significant relationship between the rotation of directors and Selic interest rates in the long run. Regarding the second estimated reaction function, it can be said that there is reaction of interest rate due to deviations between the predicted values and those if actually occurred for monetary aggregates. Although this response, it is not immediate. There is a "delay" in the central bank's reaction to these deviations. This delay in reaction of the central bank can affect the combat of the inflationary pressures and it would be interesting to more frequent monitoring of monetary aggregates in Brazil.